The Singular Capture of a Moment : Robert Schumann and Translation - Azenha Junior, João (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
This paper is part of a broader research project, which involves the translation into Brazilian Portuguese of the Gesammelte Schriften über Musik und Musiker (Collection of Writings on Music and Musicians) of the German composer Robert Schumann (1810-1856). Originally published between 1834 and 1844 in the journal Neue Zeitschrift für Musik, the texts that compose the writings were put together by Schumann himself between 1852 and 1854. Sharply attuned to the aesthetic ideals of his time, Schumann registered in his writings his impressions and comments on the musical and literary scene in the first half of the nineteenth century in Germany. This study examines On Music and Musicians with special emphasis on the reviews written between 1834 and 1836, in order to identify echoes of the main ideas on language and translation developed in Germany between the end of the eighteenth and the beginning of the nineteenth centuries. The bases for the study are two focal points, both of them brought to light by the notion of poetic creativity (Dichtung): The first one is anchored vertically and operates within the subject that moves from music to literature and vice versa, or from one language to another. The second one takes into account the shaping of the immersion into an element which will break down the barriers of time and, in one movement, bring the past into the present and include the future. In this sense, translation in Schumann’s writings is entirely imbued with the notion of movement and is regarded as a creative human activity, whose capacity to transform senses depends on one’s potentialities of using the language, thus promoting the diffusion of knowledge and the construction of identities.